Characteristics of purse seine fisheries in the Egyptian Mediterranean waters: A case study of Abu Qir Bay - EL-Sira, Ibrahim; Walid, Elsawy Aly; El-Far, Alaa; Younis, Alaa; Nasr-Allah, Ahmed (Elsevier, 2025)
This study comprehensively assesses purse seine fisheries in Abu Qir Bay, a key fishing ground on Egypt’s Mediterranean coast. The study utilized semi-structured interviews, field observations, and gear analysis to document vessel specifications, fishing operations, and catch composition for night-light and daylight purse seine fisheries. Of the nine vessels examined in the present study, five were consistent with their official designation as purse seiners, while the remaining four were recorded under alternative classifications, including longliners and trawlers. These inconsistencies suggest that economic considerations can influence fishers’ decisions regarding gear selection and operational strategies. Night-light nets measured 275–330 m in length and 91–110 m in depth, whereas daylight nets were larger (366–403 m in length) but shallower (54–70 m in depth). The main body of both net types had an 8.5 mm mesh length, which is far below sustainable recommendations. Small pelagic fishes, particularly Engraulis encrasicolus and Sardinella aurita, dominated the catch across all seasons, with night-light operations peaking in summer and daylight fishing more active in spring and autumn. While technological advancements have improved vessel efficiency and catch per unit effort, they have also intensified fishing pressure. Overfishing, overcapacity, and the use of small mesh sizes may present challenges to long-term sustainability. The results suggest opportunities to strengthen existing regulatory frameworks and to prioritize the design and enforcement of targeted management interventions. This paper recommends adopting a legal minimum mesh size of 25.7 mm and promoting an ecosystem-based management framework to help address overfishing, enhance stock productivity, and support the long-term sustainability of purse seine fisheries in Abu Qir Bay.